PELATIHAN BUDIDAYA IKAN LELE, MANAJEMEN USAHA, DAN TEKNIK PRODUKSI IKAN LELE DI GUNUNG SARIK KECAMATAN KURANJI KOTA PADANG - Imtihan Imtihan; Reffi Aryzegovina; Lisa Mayasari (Jurnal Hilirisasi IPTEKS, 2023)
Catfish cultivation is among the highly sought-after enterprises in Gunung Sarik, Padang City, yet catfish breeders generally lack knowledge and skills in catfish production techniques, including catfish farming methods and innovations in artificial feed or alternative feeds. Additionally, there is a lack of knowledge and skills in business management. The objective of this activity is to provide modeling to the related groups regarding catfish farming techniques, business management, and catfish production. This activity has been carried out within the catfish cultivation groups in Gunung Sarik, Kuranji Sub-district, Padang City. The methods employed include: (1) socialization; (2) training and mentoring; (3) monitoring and evaluation related to business management and catfish farming techniques systematically. The results indicate that the training and mentoring significantly benefit the development of catfish cultivation businesses in the Gunung Sarik catfish cultivation group. The group was able to organize and improve the quality of business management, implement alternative feed manufacturing technology, and apply proper catfish farming methods. This is evidenced by the increased catfish production by the group, leading to enhanced efficiency and sustainability of the catfish cultivation business. Therefore, it can be concluded that training and mentoring in catfish cultivation are effective strategies for developing catfish cultivation businesses and enhancing community empowerment. With the conducted transfer of science and technology, the group is capable of optimizing potential and increasing catfish production yields.